Cetuximab Can Be an Effective and Low-Toxicity Maintenance Treatment Drug in Patients With Metastatic Colorectal Cancer: A Real-World Study of Zhejiang Cancer Hospital - Yuan, Meiqin; Wang, Zeng; Zhao, Yazhen; Feng, Tingting; Lv, Wangxia; Zhong, Haijun (Frontiers in Pharmacology, 2021)
After initial treatment, maintenance therapy is now commonly used in mCRC patients, which can help patients live longer, have lower side effects and higher quality of life. Maintenance treatment may include chemotherapy, targeted therapy, or combined with chemotherapy and targeted therapy. But the evidence of cetuximab maintenance is still scant. Methods: We collected real-world data of wild-type RAS unresectable mCRC patients who were treated with cetuximab-based chemotherapy as first-line therapy between January 2013 and December 2018 at the Zhejiang Cancer Hospital (Hangzhou, China). Results: A total of 177 patients were ultimately included in the study, and 107 patients had progression information in medical records, all patients had survival data. The median OS was 40.9ms, ORR was 14.7%, and DCR was 73.5%. Subgroup analysis showed that the mOS was better in maintenance patients rather than non-maintenance(47.1ms vs 28.6ms, p=0.001), efficacy evaluation with CR+PR+SD better than PD(46.2ms vs 15.9ms, p<0.001), with primary tumor resection better than didn’t(47.1ms vs 35.4ms, p=0.038). In those 107 pts who had progression information, the median PFS was ms, and the median OS was ms, ORR was 18.7% and DCR was 84.1%. Subgroup analysis showed that the mPFS and mOS was 11.6ms and 47.1ms respectively in the maintenance group, which were significantly better than the 6.1ms and 28.7ms in the non-maintenance group (P = 0.025, 0.017, respectively). The mPFS and mOS in patients with efficacy evaluation of CR+PR+SD was 10.3ms and 47.1ms respectively, significantly better than the 2.8ms and 13.5ms in the PD patients (P = 0.012, <0.001, respectively). The mOS was the best in only lung metastases patients, patients with other organs metastases was the worst. Primary tumor site and primary tumor resection also affect the OS, primary tumor resection better than didn’t(P =0.048), left side better than right side(P <0.001). Conclusion: For patients with all RAS wildtype and initially unresectable mCRC who experienced standard first-line cetuximab-based treatment, maintenance treatment contained cetuximab can significantly improve the mPFS and mOS, and the observed toxicity was mostly mild too. So we consider cetuximab can be an effective and safety maintenance drug in mCRC patients.